Prevalence of overweight and obesity in children aged 5 to 6 years exposed to Gestational Diabetes Mellitus complicated pregnancies in the Western Cape, South Africa - Haynes, Magret C. (Division of Nursing and Midwifery, 2019)
Background: Gestational Diabetes Mellitus (GDM) has been linked with later metabolic abnormalities in offspring due to subsequent overweight and obesity. In Sub-Saharan Africa, there is a paucity of data on the outcomes of children exposed to GDM in utero. Aims: The primary aim of this sub-study was to investigate the prevalence of overweight and obesity in 5 and 6-year-old children from GDM complicated pregnancies and macrosomia at birth in the same cohort. The secondary aim was to identify risk factors associated with overweight and obesity in these 5 and 6-year-old children. Outcome measures: The main outcome was the prevalence of overweight and obesity in these children as measured by their age-specific body mass index (BMI) and Z-scores. Additionally, the association between other risk factors, overweight and obesity was investigated. Methods: A cross-sectional sub-study design was employed nested within a larger study that is investigating the progression to type 2 diabetes in women managed for GDM during 2010 and 2011. Mothers who participated in the larger study were informed about the sub-study and invited to allow their children to participate in the sub-study. Written informed consent was obtained from the mothers for the sub-study. The following data were collected: anthropometric data at birth and pregnancy related information from the mothers’ hospital record, additional demographic, social and medical information by questionnaire from the mother and at the research center. In addition, the children were weighed and had their height measured using standardized methods. Anthropometry was standardized using WHO standards. Risk factors for overweight and obesity were tested using a BMI>1 Z-score cut-off, (as a binary variable) in a manual multivariate logistic regression model. Results: The sub-study recruited 176 participants; 78 boys (44.3%) and 98 girls (55.7%). The mean (SD) Z-scores for the children’s anthropometry at ages 5 to 6 years were 0.28 (1.40) for weight, 0.01 (1.07) for height and 0.37 (1.63) for BMI. The overall prevalence of macrosomia at birth (birth weight>4000 gm) was 12.3 % (95% CI 8.2-9.1). The overall prevalence of overweight in the 5 and 6-year-old children was 13.4% (95% CI 8.6-20.4), while the prevalence of obesity was 14.2% (95% CI 9.2-21.2). The combined prevalence of overweight and obesity was 27.6% (95% CI 20.6-35.9). The prevalence of macrosomia (P=0.53) or overweight/obesity proportions (P=0.37) at ages 5 to 6 years did not differ by gender. In multivariate logistic regression analysis, factors independently associated with the risk of overweight and obesity were: mothers’ oral glucose tolerance test 2-hour blood glucose level during pregnancy (AOR=2.06, 95% CI 1.14-3.74, P=0.02), birth weight (AOR=1.00, 95% CI 1.00-1.00, P=0.01), child’s age in years (AOR=0.03, 95% CI 0.002-0.29, P=0.004) and number of adults in the house (AOR=0.38, 95% CI 0.17-0.86, P=0.02). Conclusion: This is the first study to report the prevalence of overweight and obesity in children born from GDM complicated pregnancies, in the Western Cape, South Africa. The combined prevalence of overweight and obesity found in 5 and 6-year-old children exposed to GDM in the Western Cape is higher than overweight and obesity in children reported in other South African studies. This can imply a higher tendency towards overweight and obesity in children exposed to GDM which needs further exploration.